Memórias da cidade : as ruínas da histórica Laranjeiras/SE - Feitosa, Allan Rafael Veiga (2012)
The historical and patrimonial city of Laranjeiras has as its main characteristic, the reference to an opulence moment that lived in century XIX, where printed in the Province of Sergipe Del Rey, today State of Sergipe, the mark in a typically urban way of life, that experience daily. As result of one strong economy, based on an intense commerce of merchandises and an expression of culture in bubbling. Such factors had attracted to the city a great contingent of people of next regions e, in certain measure, of Brazil; since simple workers, the men of the Brazilian colonial elite and the intellectuality of the country. However, at the beginning of century XX, the city already did not support such scene and the important conditions and elements had put that it as one of the cities richest and of the region, to the few had disappeared, together with the population that if removed in search of better chances, especially in the new Aracaju district. After some years in this situation the city collapses and more it was not risen economically, and today's Laranjeiras still lives the consequences of this breaking abrupt in the continuity of that moment. However, the city keeps alive a part of that past, through its joint architectural and urban, translated, over all, in its, constructions and ruins. This dissertation is the end item of all an inquiry carried through in the scope of the Core of After-Graduation and search in Social Sciences of the Federal University of Sergipe and considers it to argue the way as the ruins of this patrimony architectural, becomes related with the social group of that space, for the bias of the collective memory. In virtue of the accentuation of processes of urban intervention, that frequent generate social losses. Our empirical clipping understands the space of the historical center of the city, and our object is the ruins circumscribe that it. The research argues that the ruins of the historical center of Laranjeiras keep in its peculiar materiality an important one assist in the reconstitution of the imagined history of the city through shared souvenirs that by them are evoked and then in the group. Thus, such characteristics, being denied or unobserved, mainly, for the politics of patrimony in interventions of I restore, tend to breach with the history imagined (collective memory) for a quite spectacular history, anti-symmetrical the memory shared in the group. The field research had disclosed them that the narratives of memory of the inhabitants of the city are loaded of souvenirs that if relate to the patrimony of the city in ruin. The research if uses of literal elements in old periodicals, narratives of verbal memory, direct comment, beyond pairs of categories of referring social analyses the memory and the ruin. Thus, what we conclude, for our suggestion of analysis, it was that through the ruins of the historical center of Laranjeiras, which bring in itself, as are, the materiality of a past, the individuals that inhabit and experiential that space, receive the stimulations for apprehension from this past, despite they have not lived them. Such apprehension occurs through the collective memory constructed in way to the group, that frequent is used of the enrolled ruins in this space, stops for greater “ attention force ” to the one honorable time of the city, strong represented in the imagined history of the Laranjeirense society and that if not observed for the urban interventions the ballasts of memory of this image can exactly, for a quite spectacular history. As well as contribution to the quarrel of the politics of patrimony in Brazil, over all the interventions of I restore, thinking about a city constructed and lived for its inhabitants, we plead to be pertinent, to apprehend the possible relations of constructions in ruins, stops with the memory of the group circumscribes that them, and alone then, to revisit them it the light of these relations.